GREEN COSMETICS IN INDONESIA: UNRAVELING ATTITUDE-BEHAVIOR GAP AND GENDER MODERATION - Andika, Andika; Nadia, Nadia; Najmudin, Mohamad; Hasibuan, Ale Bemby (Jurnal Aplikasi Manajemen, 2023)
Green cosmetics are becoming increasingly popular as consumers' awareness of the environment grows. This study explores the relationship among Indonesian consumers' attitudes toward green cosmetics, environmental consciousness, behavioral control, subjective norms, product knowledge, purchase intention, and purchasing behavior. Data were collected from 310 respondents through an online questionnaire from various groups of men and women, then analyzed using Descriptive Statistical Analysis and SEM (Structural Equation Modeling). The research findings indicate that attitudes towards green cosmetics significantly influence purchase intention, and environmental consciousness also plays a crucial role in driving purchase intention. Perceptions of behavioral control and subjective norms also significantly affect purchase intention. Product knowledge has a significant impact on attitudes towards green cosmetics. Purchase intention significantly influences actual purchasing behavior. Exciting differences are observed between men and women. Environmental consciousness significantly impacts women's purchase intention, while behavioral control and subjective norms are more dominant in influencing men's purchase intention. The implications of this research are essential for producers and marketers of green cosmetics, offering insights for developing effective marketing strategies. This study highlights the importance of different approaches when targeting male and female consumers, considering the factors influencing their purchase intentions and behavior. These findings contribute to a deeper understanding of consumer behavior related to green cosmetics, encouraging environmentally friendly consumption patterns.